Improved light extraction efficiency of GaN-based vertical LEDs using hierarchical micro/subwavelength structures. (14th April 2015) - Kang, Eun Kyu; Kwon, Eunhee; Min, Jung Wook; Song, Young Min; Lee, Yong Tak
Abstract: We demonstrate the hierarchical micro- and subwavelength-structures on the surface of GaN based green vertical light-emitting diodes (VLEDs) to enhance the light extraction efficiency. Hierarchical structures (HSs), which were fabricated by simple two-step process consisting of pattern transfer of reflowed photoresist for micro structures (MSs) and self-masked dry etching method for subwavelength structures (SWSs), play an important role in enhancing the light extraction efficiency by reducing both the total internal reflection and the Fresnel reflection. HSs lead to an enhancement of optical output power of ∼200% compared to the conventional VLEDs with flat surface as a result of reflection suppression and transmittance enhancement, without any serious degradation of electrical characteristics and a change of peak emission wavelength as function of injection current. Furthermore, optical simulations by ray-tracing and the rigorous coupled-wave analysis methods provide design guidelines for MSs and SWSs, respectively.